Work situation of women in the gravidic-puerperal cycle - de Godoy, Maria Beatriz; Gomes, Flávia Azevedo; Stefanello, Juliana; dos Santos Monteiro, Juliana Cristina; Spanó Nakano, Ana Márcia (Investigación y Educación en Enfermería, 2011)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To characterized the work situation of women in the gravid-puerperal cycle. Methodology. Transversal study, performed in 2005 in a maternal unit in Riberirao Preto- Brazil that attends exclusively patients from the Unique Health System. 122 postpartum women who were in the labor market during pregnancy participated. Results. 52.5% of the participants had remunerated activities, of which 45.3% were informal activities. Pregnancy was the reason for firing 79.3% of the women. When they finish their maternity license, women will have to assume their domestic and family duties beside the ones from the remunerated work ones. Conclusion. Work situation of the studied population is not always favorable to the exercise of civil rights what ends in unemployment and work desertion.